Differentiation of Slovak and Tunisian Castor Genotypes (Ricinus communis L.) Using SCoT Markers - Vivodík, Martin; Petrovičová, Lenka; Balážová, Želmíra; Gálová, Zdenka (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The characterization of genetic diversity of genotypes is the basic prerequisite for the successful breeding programs of castor like other crops. In the present investigation 40 genotypes of castor were analysed using 10 start codon targeted (SCoT) markers. Ten primers produced 62 DNA fragments with an average of 6.20 bands per primer. From these ten primers, primer SCoT 65, were the most polymorphic, where 7 polymorphic amplification products were detected. The lowest number of amplified polymorphic fragments (3) was detected by primer SCoT 66. From the 62 amplified bands, 48 (85.94 %) were polymorphic, with an average of 4.80 polymorphic bands per primer. To determine the level of polymorphism in the analysed group of castor genotypes, polymorphic information content (PIC) was calculated. The polymorphic information content (PIC) value ranged from 0.652 (ScoT 8) to 0.816 (SCoT 23) with an average of 0.738. The dendrogram of genetic relationships among 40 castor genotypes based on SCoT markers was constructed. The hierarchical cluster analysis showed that the castor genotypes were divided into 3 main clusters. Cluster 1 contained one Tunisian castor genotype KJ-2. Cluster 2 contained 2 castor genotypes RM-84 and RM-94. Cluster 3 was divided into subcluster 3A and subcluster 3B. Subcluster 3A contained 2 Tunisian castor genotypes- KJ-3 and KJ-4. Subcluster 3B contained 35 genotypes of castor. Two Tunisian castor genotypes of 3B subcluster (KJ-1 and KJ-5) were genetically the closest. We can assume that they have close genetic background. The present study shows effectiveness of employing SCoT markers in analysis of castor, and would be useful for further studies in population genetics, conservation genetics and genotypes improvement.